Acknowledged attributes by students about the physical education teacher (Impetus, 2024)
Physical education from the perspective of the student and the suggestions to improve them. The study was framed in the multi-method design. The collection of information was carried out through a semi-structured survey with closed and open questions about the characteristics of the physical education teacher and about the qualities that a good PE teacher should have. With open questions such as what do you like most about the physical education class? and how would you improve the physical education subject? These questions were asked of 2,550 students in the grades ninth and tenth of the nine (9) subregions of the Department of Antioquia (Colombia) It was found that a large part of the students saw as positive the good attitude of theteacher, the way in which he teaches, the explanation and the respect towards them. The students recommend that teachers should improve clarity and objectivity when explaining content, make them understand the importance that physical education has and finally, improve the attitude in the class. These attributes highlighted by the students could contribute to improving the classroom environment.
Keywords: Teacher attitude; teacher explanation; teaching; high school students